Desain dan analisis pengaruh parameter PI dan variasi kecepatan pada respon sistem kontrol arah hadap prototype kendaraan listrik - Afif Caesar Distara; Fatkhur Rohman (Universitas Muhammadiyah Metro, 2020)
Electric vehicles are alternative vehicles that carry energy efficient. At this time the dominant vehicle uses ordinary wheels so that it will become an obstacle in the maneuver function that requires movement in various directions. With mechanum wheels the vehicle can move in various directions by adjusting the direction of rotation of each wheel. The problem is choosing the right control system for the control system needed by the vehicle. The purpose of this study is to determine and analyze the effect of variations in the value of PI (Proportional Integral) and speed of the vehicle to the stability response of the system to control the direction of prototype electric vehicles. This study method is an experiment that is by giving a treatment, then evaluating the effects caused by the research object. The results of this study can be concluded that the variation of PI constant values and speed variations have an effect on the stability parameters of the system, namely rise time, settling time, overshot, and steady state error. To get the best system stability response results can use the constant value PI Kp = 2; and Ki = 17; where the stability response of the system for direction control at each speed condition has a fairly good value with a fast rise time, fast settling time, small overshot and a small error steady state compared to other PI constant values in this study.Keywords: mechanum wheel, PI control, direction, prototype, system stability